The association of food insecurity with the quality of life, academic performance and body mass index among university students - Ahmad Nadzri, Nur Farihah; Mohd Shukri, Nor Azwani; Mohd Abu Bakar, Wan Azdie (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Introduction: Food insecurity is a condition which occurs when people lack access to adequate amount of safe and nutritious food for healthy life. University students are vulnerable to food insecurity but not many studies emphasize on the relationship between food insecurity and the quality of life (QOL), academic performance as well as body mass index (BMI) level in Malaysia. Therefore, this study was designed to determine the association of food insecurity with the QOL, cumulative grade point average (CGPA) score and BMI level among the International Islamic University Malaysia Kuantan campus students. Methods: A total of 362 respondents were recruited and 310 completed a questionnaire that consisted of three parts which were the socio-demographic profile, Food Insecurity Experience Scale (FIES) and WHOQOL-BREF questionnaire. Weight and height were measured using standard anthropometry instruments and techniques. Results: It was found that 30.6% of respondents were food insecure with 24.8% were categorized as having moderate food insecurity and 5.8% severe food insecurity. However, food insecurity was not associated with either QOL, CGPA score or BMI level. Conclusions: Food insecurity among students is a serious issue. The prevalence was found to be quite high in this study for which interventions should be explored. Further research on the relationship between food insecurity and QOL, CGPA as well as BMI level among tertiary education institution students is also needed.